2023
DOI: 10.3390/ijerph20115939
|View full text |Cite
|
Sign up to set email alerts
|

Gardening in Childcare Centers: A Randomized Controlled Trial Examining the Effects of a Garden Intervention on Physical Activity among Children Aged 3–5 Years in North Carolina

Abstract: This study examined the effects of a childcare gardening intervention on children’s physical activity (PA). Eligible childcare centers were randomly assigned to: (1) garden intervention (n = 5; year 1); (2) waitlist control (n = 5; control year 1, intervention year 2); or (3) control (n = 5; year 2 only) groups. Across the two-year study, PA was measured for 3 days at four data collection periods using Actigraph GT3X+ accelerometers. The intervention comprised 6 raised fruit and vegetable garden beds and a gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The NC study reported significant intervention effect for MVPA (p < 0.0001) and sedentary minutes (p = 0.0004), with children at intervention (gardening) centers acquiring approximately 6 min more MVPA and 14 min less sedentary time each day while attending their respective childcare centers (school time) [10]. We did not find any significant differences (p = 0.15) between the experimental (gardening) and the control (non-gardening) group (Table 6 and Figure 4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The NC study reported significant intervention effect for MVPA (p < 0.0001) and sedentary minutes (p = 0.0004), with children at intervention (gardening) centers acquiring approximately 6 min more MVPA and 14 min less sedentary time each day while attending their respective childcare centers (school time) [10]. We did not find any significant differences (p = 0.15) between the experimental (gardening) and the control (non-gardening) group (Table 6 and Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…Analyzing data at these three levels make this study unique compared to relevant other contemporary research. The NC study [10] investigated similar effects only during school time (accelerometers were taken off before leaving childcare facilities) but it emphasized the need for investigating potential 'spillover effects' beyond school time at home. This study attempted to investigate this 'spillover effect' [23] by collecting PA data of children beyond school time while they were engaged in hands-on gardening at their respective childcare centers (Experimental Group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NC study reported a significant intervention effect for MVPA (p < 0.0001) and sedentary minutes (p = 0.0004), with children at intervention (gardening) centers acquiring approximately 6 min more MVPA and 14 min less sedentary time each day while attending their respective childcare centers (school time) [11]. We did not find any significant differences (p = 0.15) between the experimental (gardening) and the control (non-gardening) group (Table 7 and Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Hands-on gardening, which is found to be associated with higher levels of PA for adults [6,7] and school-agers [8,9] can also be an effective intervention-based obesity prevention technique during early childhood. Two recent studies conducted in North Carolina (NC) [10,11] found positive associations between hands-on gardening and both PA and healthy eating preferences for preschoolers attending centerbased childcare. These are among the very few studies that investigated the potential role of gardening in licensed center-based childcare facilities for preventing obesity during the early years of childhood.…”
Section: Introductionmentioning
confidence: 99%